Altitudinal distribution of native and alien plant species in roadside communities from central Argentina - Paiaro, Valeria (2011)
Roadsides may homogenize the distribution of native species and act as corridors for the spread of alien taxa. We examined the variation in native and alien plant species richness and composition at two spatial scales defined by altitude and habitat type (edges and fill slopes), as well as the relationship between native and exotic species richness in roadside plant communities in mountains from central Argentina. Following a gradient from 1100 to 2200 m a.s.l. along a mountain road, plant species cover was recorded within sample plots of 30 m × 10 m systematically located at 100-m altitude intervals on both roadside habitats. Although native species richness decreased with altitude and composition changed accordingly, the number of alien species peaked at both extremes of the elevation gradient and did not reflect an altitudinal replacement of chorological groups. The number of both native and alien species was higher in roadside edges, but a negative association between the richness of native and alien species occurred only on fill slopes, suggesting that roadside habitats differ in their susceptibility to plant species colonization and in the mechanisms driving native and alien species richness. Our results highlight the importance of altitude and roadside habitat as factors controlling plant species richness and composition along roadside communities in central Argentina. Although altitude acts as a filter for native plants, it apparently did not constrain the establishment of alien species along the studied roadsides, indicating that the influence of this road as a plant species corridor may increase with time, promoting the opportunities for aliens to expand their current distribution.